Gnathia masca sp. nov. (Crustacea, Isopoda, Gnathiidae) from Lizard Island, Great Barrier Reef, Australia - Farquharson, Charon; Smit, Nico J.; Grutter, Alexandra S.; Davies, Angela J. (Zootaxa, 2012)
Gnathia masca sp. nov. is described from material collected off Coconut Beach, Lizard Island, Great Barrier Reef, Aus-tralia. Males are characterised by a cephalosome with a shallow dorsal sulcus that stretches half its length, a slightly pro-duced frontal border with two conical superior fronto-lateral processes and a conical inferior medio-frontal process. Malemandibles have 6 processes on the dentate blade and a distinct internal lobe with 6 or 7 crenulations and a single largedistal process. Live males, females and larvae are characterized by brown pigmentation especially in the male where it forms a dark band that stretches between the eyes, giving it the appearance of a mask.